Use of banana diversity for nutritious diets - Bioversity International (2015)
Vitamin A deficiency (VAD) is the leading cause of preventable blindness in children, with an estimated 250,000-500,000 children becoming blind every year. Half of them die within 12 months of losing their sight, as VAD increases the risk of disease and death from severe infections. In pregnant women, VAD causes night blindness and may increase the risk of maternal mortality. VAD is a public health problem in more than half of all countries, especially in Africa and South-East Asia.